Labouring Together: collaborative alliances in maternity care in Victoria, Australia—protocol of a mixed-methods study. Issue 3 (7th March 2017) - Watkins, Vanessa; Nagle, Cate; Kent, Bridie; Hutchinson, Alison M
Abstract : Introduction: For over a decade, enquiries into adverse perinatal outcomes have led to reports that poor collaboration has been detrimental to the safety and experience of maternity care. Despite efforts to improve collaboration, investigations into maternity care at Morecambe Bay (UK) and Djerriwarrh Health Services (Australia) have revealed that poor collaboration and decision-making remain a threat to perinatal safety. The Labouring Together study will investigate how elements hypothesised to influence the effectiveness of collaboration are reflected in perceptions and experiences of clinicians and childbearing women in Victoria, Australia. The study will explore conditions that assist clinicians and women to work collaboratively to support positive maternity outcomes. Results of the study will provide a platform for consumers, clinician groups, organisations and policymakers to work together to improve the quality, safety and experience of maternity care. Methods and analysis: 4 case study sites have been selected to represent a range of models of maternity care in metropolitan and regional Victoria, Australia. A mixed-methods approach including cross-sectional surveys and interviews will be used in each case study site, involving both clinicians and consumers. Quantitative data analysis will include descriptive statistics, 2-way multivariate analysis of variance for the dependent and independent variables, and χ 2 analysis to identify the degree of congruence between consumer preferences and experiences. Interview data will be analysed for emerging themes and concepts. Data will then be analysed for convergent lines of enquiry supported by triangulation of data to draw conclusions. Ethics and dissemination: Organisational ethics approval has been received from the case study sites and Deakin University Human Research Ethics Committee (2014–238). Dissemination of the results of the Labouring Together study will be via peer-reviewed publications and conference presentations, and in written reports for each case study site to support organisational change.